The new keynesian approach to dynamic general equilibrium modeling: Models, methods, and macroeconomic policy evaluation - Sebastian Schmidt; Volker Wieland (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2012)
This chapter aims to provide a hands-on approach to New Keynesian models and their uses for macroeconomic policy analysis. It starts by reviewing the origins of the New Keynesian approach, the key model ingredients and representative models. Building blocks of current-generation dynamic stochastic general equilibrium (DSGE) models are discussed in detail. These models address the famous Lucas critique by deriving behavioral equations systematically from the optimizing and forward-looking decision-making of households and firms subject to well-defined constraints. State-of-the-art methods for solving and estimating such models are reviewed and presented in examples. The chapter goes beyond the mere presentation of the most popular benchmark model by providing a framework for model comparison along with a database that includes a wide variety of macroeconomic models. Thus, it offers a convenient approach for comparing new models to available benchmarks and for investigating whether particular policy recommendations are robust to model uncertainty. Such robustness analysis is illustrated by evaluating the performance of simple monetary policy rules across a range of recently-estimated models including some with financial market imperfections and by reviewing recent comparative findings regarding the magnitude of government spending multipliers. The chapter concludes with a discussion of important objectives for on-going and future research using the New Keynesian framework.
urn:nbn:de:hebis:30:3-252562
Keywords: C51; C52; C61; C68; E12; E17; E52; E63; 330; Monetary macroeconomics; Keynesian models; New Keynesian models; dynamic stochastic general equilibrium models; New Neoclassical synthesis; model comparison; rational expectations; policy evaluation; policy robustness; monetary and fiscal policy